Comparative evaluation of Subepithelial Connective Tissue Graft (SCTG) and Acellular Dermal Matrix Allograft (ADMA) in the treatment of localized gingival recession- A clinical study - A B Tarun Kumar; D S Mehta (Wolters Kluwer Medknow Publications, 2009)
Gingival recession is the one of the commonest clinical features of chronic periodontitis and poses a great esthetic and functional problem to the patient. Several treatment modalities have been described in the dental literature to treat the localized gingival recession. In the present study, the efficacy of subepithelial connective tissue graft (SCTG) and the acellular dermal matrix allograft (ADMA) was evaluated and compared in the treatment of localized gingival recession. Nine patients with bilateral identical Miller's class I or II were selected and randomly assigned to treatment with either SCTG or the ADMA. Six months follow-up result showed significant clinical outcome in both the treatment groups in terms of improvement in recession depth, root coverage percentage, probing depth, clinical attachment level and the width of keratinized tissue. However on comparison between the two groups, no significant difference was found in relation to any of the parameters. Hence, it can be concluded that both the techniques (SCTG & ADMA) are equally effective in the treatment of localized gingival recession and restoring the esthetic and function.